2011
DOI: 10.4028/www.scientific.net/amr.324.181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Residual Deformation on the Mechanical Behavior of the Ni-Ti Alloy Charged by Hydrogen

Abstract: Because of its good corrosion resistance and biocompatibility, superelastic Ni-Ti wire alloys have been successfully used in orthodontic clinics. However, delayed fracture in the oral cavity has been observed. The susceptibility of a Ni–Ti shape memory alloy towards hydrogen embrittlement has been examined with respect to the residual stress after a few numbers of cycles and ageing in air at room temperature. Orthodontic wires have been cathodically charged by hydrogen with a current density of 10 A/m2 from 4h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This observation is explained by the presence of hydrogen that blocks the motion of the Ni and the Ti. Consequently, they retard the occurrence of the martensite transformation and contribute to its hindrance [4,27]. Moreover, it is observed that during the plateau, the fluctuation has been heightened.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is explained by the presence of hydrogen that blocks the motion of the Ni and the Ti. Consequently, they retard the occurrence of the martensite transformation and contribute to its hindrance [4,27]. Moreover, it is observed that during the plateau, the fluctuation has been heightened.…”
Section: Resultsmentioning
confidence: 99%
“…However, we notice that the hardening-like slope of the phase-transformation pseudo-plateau grows slightly and a minor reduction of the plateau is detected. According to our previous results [5][6][7], this could be attributed to the hindrance of the austenite transformation by the absorbed hydrogen. In addition, this result indicates that after 3 h of immersion, the amount of diffused hydrogen is not enough to cause an increase in the critical stress for introducing martensite or to generate an embrittlement during the austenite transformation.…”
Section: Methodsmentioning
confidence: 99%
“…This behaviour was attributed to the accumulation of hydrogen atoms, preferentially within regions that contain continual deficiencies, because of being trapped by retained martensite plates and dislocations, forming an obstacle which would cause fracture when the martensite domains were forced to pass across these boundaries [ 11 ]. In several studies [ 16 , 17 ], permanent defects could be obtained by cyclic deformation. In [ 18 ], the authors indicated that the pseudo-elastic hysteresis loops would decrease as the number of cycles increased and the strain hardening slope grew.…”
Section: Introductionmentioning
confidence: 99%